Upaya Meningkatkan Hasil Belajar Matematika dengan Metode Demonstrasi Siswa Kelas VI.A SD Negeri 30 Cakranegara - Hernatih, Hernatih (TSAQOFAH, 2023)
The purpose of this research is to find out that using the demonstration method can improve the learning outcomes of students in class VI.A SD Negeri 30 Cakranegara Odd Semester 2022/2023 Academic Year. The research was conducted in class VI.A with a total of 27 students, consisting of 11 male students and 16 female students. The design used in this study was using classroom action research (CAR) using two cycles, each cycle consisting of two meetings. Observation and test collection methods. The instruments used were student activity observation sheets and student learning outcomes assessment sheets. The data obtained using qualitative analysis and quantitative descriptive. The demonstration method can improve mathematics learning outcomes regarding calculating area in class VI.A students of SD Negeri 30 Cakranegara, this can be proven by the results of the study showing that the level of completeness of student learning outcomes increased from 62.96% before the action to 81.48% in the cycle I and became 100% in cycle II. The conclusion of this study is that the demonstration method can improve student learning outcomes in learning Mathematics on the material for calculating area in class VI.A SD Negeri 30 Cakranegara in the 2022/2023 academic year.